Numerical simulation study of the effect of integrating hemp concrete and passive strategies on the energy consumption of a residential building in Al-Hoceima - Kaddouri, Hicham; ABIDOUCHE, Abderrahim; SAIDI HASSANI ALAOUI, Mohamed; DRIOUCH, Ismael; Ait Msaad, Abdelouahad; HAMDAOUI, Said (Statistics, Optimization & Information Computing, 2024)
In this work, we present an energy efficiency study for a residential building located in the city of Al-Hoceima, Morocco. The aim is to bring the building into compliance with the technical requirements of the Moroccan Thermal Building Regulations (RTCM). To achieve this, several modifications and interventions were carried out, such as the use of hemp concrete for insulation and the integration of passive strategies to minimize energy loads. Similarly, this energy study is carried out as a simulation using TRNSYS software, so that the building is modeled as a multizone entity with an occupancy schedule. The simulation results show that the technical requirements of the RTCM are achieved using a construction containing hemp concrete with an optimum thickness of around 10cm, this thickness can be reduced to 4cm using double glazing, or to 1cm using controlled natural ventilation in summer and winter.